2005
DOI: 10.1104/pp.104.050914
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomics of the Regulation of the Nitrate Assimilation Pathway in Chlamydomonas

Abstract: The existence of mutants at specific steps in a pathway is a valuable tool of functional genomics in an organism. Heterologous integration occurring during transformation with a selectable marker in Chlamydomonas (Chlamydomonas reinhardtii) has been used to generate an ordered mutant library. A strain, having a chimeric construct (pNia1::arylsulfatase gene) as a sensor of the Nia1 gene promoter activity, was transformed with a plasmid bearing the paramomycin resistance AphVIII gene to generate insertional muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 50 publications
(13 reference statements)
3
90
1
Order By: Relevance
“…The number of integrations was calculated using the delta Ct method [38] and specific primers of very similar efficiencies for AphVIII and Nia1 ( Table I). Efficiencies of the primers were previously determined [21]. We found that practically all of the mutants analyzed had a single copy of the tag DNA in their genomes.…”
Section: Identification Of the Genomic Regions Flanking The Insertionmentioning
confidence: 86%
See 4 more Smart Citations
“…The number of integrations was calculated using the delta Ct method [38] and specific primers of very similar efficiencies for AphVIII and Nia1 ( Table I). Efficiencies of the primers were previously determined [21]. We found that practically all of the mutants analyzed had a single copy of the tag DNA in their genomes.…”
Section: Identification Of the Genomic Regions Flanking The Insertionmentioning
confidence: 86%
“…In mutants B20 and M2 several attempts did not yield any amplification. This could mean that the insertion has taken place in a region of low accessibility or that silencing epigenetic phenomena that modify the structure of the marker gene are interfering with the alignment of primers during PCR amplifications as proposed by González-Ballester and coworkers [21]. In mutant D45, predicted region coincides with the region of the chromosome 8, where is located the promoter of the Hsp70A gene and within the region of chromosome 2 corresponding to the RbcS2 promoter, which are part of the same insertional cassette, indicating the possible insertion of several tandem copies of the marker gene, as was already predicted when determining the number of integrations.…”
Section: Identification Of the Genes Responsible For The Observed Phementioning
confidence: 99%
See 3 more Smart Citations